Teacher training at a rural school in Mato Grosso do Sul – Brazil: the presence/absence of inclusive and intercultural perspectives - Luiz Henrique Poloni; Washington Cesar Shoiti Nozu; Andressa Santos Rebelo (Revista Brasileira de Educação do Campo)
In this text, the objective is to characterize the initial and continuing training of teachers at a school in the countryside of Mato Grosso do Sul, Brazil, with a view to identifying the presence/absence of inclusive and intercultural perspectives in their training paths. To this end, it is configured as a qualitative research, with a rural school located in a rural district of Mato Grosso do Sul, in the Região da Grande Dourados, as the research locus. The group of participants comprised eight teachers from the Initial Years of Elementary School. To produce data, a questionnaire with closed and open questions was used. The analyzes occurred through two axes defined a priori: one related to initial training and the other related to continuing training. The results indicated that all teachers have initial training at a higher education level and, among the eight, seven have continued training in specialization courses. In the training paths, themes related to inclusion were more present when compared to content related to interculturality. In view of the context investigated, we advocate the expansion of the debate on inclusive and intercultural education in the in-service training of rural school teachers, in order to contribute to concepts and practices that promote the articulation between the principles of equality and difference.